Essays in applied economics - Jean-Victor Alipour (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2023)
This thesis consists of five independent chapters, studying how economic agents respond to unanticipated shocks. Chapter 1 shows that a well-intentioned policy can create unintended barrier to voting by creating seemingly small shocks to voting costs. Election administrators in Munich control precinct size and recruit new polling places to improve voting accessibility, producing variation in the assignment of citizens to polling locations. Event study estimates suggest that moving a polling place causes a persistent shift from in-person to mail-in voting and a transitory drop in total turnout. The results are consistent with inattention to reassignments, causing some voters to miss requesting mail-in ballots and temporarily abstain from voting. Chapters 2-4 study the role of working from home (WFH) in the context of the economic shock induced by the Covid-19 pandemic. Chapter 2 documents inequalities in access to remote work across the economy. Chapter 3 demonstrates that WFH is an effective mitigation policy against a pandemic as it allows firms to reduce infection risk while maintaining business operations. Chapter 4 provides first insights into how the persistent shift toward remote work redistributes alters the geography of offline consumption within German cities. Difference-in-difference estimates suggest that areas with a greater scope to expand WFH experience a lasting increase in local consumer spending. Finally, Chapter 5 studies the consequences of the technological disruption caused by the advent of first-generation broadband internet for world trade. I present a Ricardian model of comparative advantage, predicting that countries with a more developed broadband network specialize in complex goods. Gravity estimates based on bilateral trade among more than 100 countries between 1998 and 2016 support the theory. – – Diese Dissertation besteht aus fünf unabhängigen Kapiteln. Kapitel 1 zeigt, dass eine wohlwollende Politik Hürden für die Wahlbeteiligung schaffen kann, indem sie vermeintlich geringfügige Schocks in den Wahlkosten verursacht. Um die Teilnahme an Wahlen zu vereinfachen, reguliert das Münchner Wahlamt die Größe von Stimmbezirken und rekrutiert neue Wahllokale, was zu Neuzuweisung von Bürgern zu Wahllokalen führt. Event-Study-Schätzer zeigen, dass die Verlegung eines Wahllokals zu einer dauerhaften Verschiebung von Urnen- zu Briefwahl und einem temporären Rückgang der Gesamtwahlbeteiligung führt. Die Ergebnisse deuten auf Unaufmerksamkeit gegenüber Neuweisungen, wodurch einige Wähler die Briefwahl-Beantragung versäumen und vorübergehend nicht an Wahlen teilnehmen. Die Kapitel 2-4 untersuchen die Rolle von Homeoffice im Zusammenhang mit der Covid-19 Krise. Kapitel 2 dokumentiert Ungleichheiten im Zugang Homeoffice. Kapitel 3 zeigt, dass Homeoffice eine wirksame Eindämmungspolitik gegen eine Pandemie ist, da sie Firmen ermöglicht, Infektionsrisiken zu reduzieren und den Betrieb aufrechtzuerhalten. Kapitel 4 präsentiert erste Erkenntnisse, wie die anhaltende Verschiebung zur Telearbeit die Geografie des stationären Konsums in deutschen Städten verändert. Difference-in-differences-Schätzer legen nahe, dass Gebiete mit größerem Potenzial zur Homeoffice-Ausweitung einen anhaltenden Anstieg im lokalen Konsum verzeichnen.
Keywords: D72; F14; I18; J30; R12; 330; Elections; remote work; broadband; consumer spending; international trade; Covid-19